The Evolution of Imaging Markers in Cardiovascular Evaluation of Patients with Hematological Malignant Neoplasia - Deman, Flavia; Andor, Minodora; Ionita, Ioana; Caruntu, Florina; Buda, Valentina; Tomescu, Mirela Cleopatra (International Journal of Innovative Research in Medical Science, 2022)
Chemotherapy-induced cardiotoxicity is a major cause of morbidity and mortality in cancer survivors. Myocardial dysfunction is one of the most frequent problems of chemotherapy, with highly important unfavorable effects on the prognosis in the short and long term. Its association with malignant pathology influences the compliance with specific oncological therapy and the healing process as well. Therefore, the myocardial dysfunction is becoming a reason for expanded morbidity and even early mortality for this category of patients. Our study demonstrates that cytostatics in the anthracycline class, especially Doxorubicin with a cumulative dose of more than 400 mg/m2, their association with "targeted" molecular therapies and Cyclophosphamide, along with the co-existence of cardiovascular risk factors such as hypertension and dyslipidemia, can affect longitudinal myocardial mechanics, which can be studied and tracked by decreasing the LSsubendo echocardiographic parameter in the first 12 months of cytostatic treatment. After the 6th dose of chemotherapy, approximately 50% of the patients under study had pathological changes in LSsubendo, and after the 8th treatment this number rose to 88%. In our study we demonstrated that the reduction in GLS between the two evaluated moments, pre-treatment and after 12 months, was influenced by the treatment with anthracyclines, with Doxorubicin administered in a cumulative dose > 400 mg/m2, with the association of cytostatic classes consisting of: anthracyclines, "targeted" molecular therapies, and cyclophosphamide, and by the coexistence of hypertension and dyslipidemia. Our results on the variation of GLS and LSsubendo at 12 months of the research for patients with hematological neoplasia are consistent with other data in literature, with myocardial deformity parameters changing early during cytostatic specific treatment, thus preceding a decline in LVEF. An early diagnosis of myocardial dysfunction is feasible by using longitudinal deformation criterion (parameters) assessed by 2D speckle tracking echocardiography.